اثر إدارة الموارد البشرية الإلكترونية على تحقيق الابداع الإداري في شركات التمويل بسلطنة عُمان: The Impact of Electronic Human Resources Management on Achieving Administrative Creativity on Finance Companies in the Sultanate of Oman - Isa bin Fadhil bin Saif al-Hosni; Abdul Kadir, Fakhrul Adabi (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2024)
This study aimed to identify the impact of electronic human resources management in terms of its dimensions (electronic recruitment and selection, electronic training, electronic performance evaluation, electronic communication) on administrative creativity in finance companies in the Sultanate of Oman. The problem of the study lies in searching for ways that push the organization towards development and success. Through the element of excellence, the most important of these means is administrative creativity. The importance of the study lies in focusing on the dimensions of electronic human resources management as one of the proposed alternatives and trying to harness it in enhancing administrative creativity at the level of finance companies in the Sultanate of Oman. The researcher followed the descriptive analytical approach, and the study was conducted on a random sample. The study population consisted of all employees of finance companies in the Sultanate of Oman, who numbered (350) employees. The sample was selected and distributed electronically according to the sample size determination table developed by Cressy and Morgan, which consisted of (224) employees. The study concluded with a set of results, the most prominent of which is that there is a statistically significant effect at a significant level (α ≤ 0.05) of electronic human resources management in terms of its dimensions (electronic recruitment and selection, electronic training, electronic performance evaluation, electronic communication) on administrative creativity in finance companies in the Sultanate of Oman. The study recommended several recommendations, the most prominent of which were: the necessity of working to increase interest by the company’s management in conducting a careful analysis of the external environment when planning electronic human resources.